Complementary Lock‐and‐Key Ligand Binding of a Triplet Transmitter to a Nanocrystal Photosensitizer. (12th April 2017) - Li, Xin; Fast, Alexander; Huang, Zhiyuan; Fishman, Dmitry A.; Tang, Ming Lee
Abstract: Owing to the difficulty in comprehensively characterizing nanocrystal (NC) surfaces, clear guidance for ligand design is lacking. In this work, a series of bidentate bis(pyridine) anthracene isomers (2, 3‐PyAn, 3, 3‐PyAn, 2, 2‐PyAn) that differ in their binding geometries were designed to find the best complementary fit to the NC surface. The efficiency of triplet energy transfer (TET) from the CdSe NC donor to a diphenylanthracene (DPA) acceptor mediated by these isomers was used as a proxy for the efficacy of orbital overlap and therefore ligand binding. 2, 3‐PyAn, with an intramolecular N–N distance of 8.2 Å, provided the best match to the surface of CdSe NCs. When serving as a transmitter for photon upconversion, 2, 3‐PyAn yielded the highest upconversion quantum yield (QY) of 12.1±1.3 %, followed by 3, 3‐PyAn and 2, 2‐PyAn. The TET quantum efficiencies determined by ultrafast transient absorption measurements showed the same trend.